Educating for values: a narrative-centred approach (Praxis Educativa, 2012)
"Men for Democracy" - a piece of research work - has ied up to the elaboration of a didactic approach which makes use of narrative for the development of values. The point of departure is not everyday ordinary matters and situations (family, school, governmental institutions) but myths, bearers of symbolic tools with a high level of abstraction but easily understood in narrative contexts which favor the construction of meaning. In narration, canonical issues (what is habitual or customary) have been transgressed, giving way to exceptional issues which in turn result in stories that act as a link between the world of culture and the world of wishes, beliefs and hopes. Myth favors reflection upon values. The spiral method goes from the reflection on mythical action to the reflection of actors on their own actions and enables metacognition. At the same time, school opens spaces so that students can make interchanges and allows for a favorable institutional atmosphere open to participation and decision-taking because relationships are horizontalised as to power distribution. The result is real learning that students can transfer to their future life as citizens. The methodology for ethical and citizen education is characterized by a selection of didactic devices which activate action and reflection, by contents organized in a recurrent way and a system of evaluation interwoven with learning.
Keywords: education; ethics; citizenship; narrative; methodology